The Impact of Family Confidence on Foot Care Behavior by Family Members Suffering from Diabetes Mellitus - Huda, Nuh; Sukartini, Tintin; Pratiwi, Sherley Ajeng; Irawandi, Dedi (International Journal of Psychosocial Rehabilitation, 2020)
Family confidence in caring for family members suffering from diabetes is an important determinant in improving foot care behavior. The purpose of this study was to determine the impact of family confidence in caring for family members suffering from diabetes on foot care behaviors. This study uses observational analytic with cross-sectional method, 126 family samples were gathered through the random sampling method; the independent variable is family confidence and the dependent variable is foot care behavior. The instrument used was the foot care confidence scale (FCCS) to assess family confidence and foot care behavior scale (FCBS) to assess foot care behavior by family. The analysis used was the Spearman correlation test. The results of the research data are high family confidence of 119 (94.4%), low family confidence 7 (5.6%); low destructive behavior, 111 (88.1%) and high destructive behavior, 15 (11.9%). This research analysis uses Spearman rank test, the results are p = 0.009 ( <0.05) r = -,532 so there is a correlation between family confidence and foot care behavior. Caring for family members who have diabetes, the lower the destructive behavior of family members, which means the behavior of caring for the feet of family members who have diabetes the better. Another impact of high family confidence is forming positive thinking patterns and self-confidence in his ability to deal with diabetes, as well as increasing motivation and support among family members.